1946
DOI: 10.1021/i560159a018
|View full text |Cite
|
Sign up to set email alerts
|

Microdetermination of Halogens and Sulfur. Using the Grote Combustion Apparatus

Abstract: Automatic combustion methods for the determination of sulfur, chlorine, bromine, and iodine are described. By the use of a modified Grote combustion tube in combination with volumetric procedures, satisfactory micromethods have been developed. The indicators used are dipotassium rhodizonate lor sulfur, dichlorofluorescein for chlorine and bromine, and starch solution for iodine. The largest standard deviation for these methods was found to be ±0.14% for sulfur, ±0,10% for chlorine, ±0.17% for bromine, and ±0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1951
1951
1982
1982

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The dust rate was estimated by comparing the sulfur weight on 2 samples each of 50 laboratorytreated leaf discs with the sulfur on 2 samples of 50 leaf discs taken from freshlytreated (6.8 kg/acre) vineyard leaves (Sundberg & Royer, 1946). bean leaf discs treated with distilled water or various formulations of sulfur: dust, micronized wettable powders, and flowable sulfurs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dust rate was estimated by comparing the sulfur weight on 2 samples each of 50 laboratorytreated leaf discs with the sulfur on 2 samples of 50 leaf discs taken from freshlytreated (6.8 kg/acre) vineyard leaves (Sundberg & Royer, 1946). bean leaf discs treated with distilled water or various formulations of sulfur: dust, micronized wettable powders, and flowable sulfurs.…”
Section: Methodsmentioning
confidence: 99%
“…These rates and formulations were: Cosan (micronized sulfur, 80 WP) 240, 480 and 960 g/100 I water; FMC (wettable sulfur, 92 WP) 300, 600, and 1200 g/100 1 water: THAT (flowable, 52% AI) 125,250, 500 ml/100 1 water; lime sul-fur (Orthorix calcium polysulfides, 26 EC) 0.97, 1.95, and 3.9 ml/100 1 water; and sulfur (dust) 6.8 kg/acre (= 0.4 hectare). The dust rate was estimated by comparing the sulfur weight on 2 samples each of 50 laboratorytreated leaf discs with the sulfur on 2 samples of 50 leaf discs taken from freshlytreated (6.8 kg/acre) vineyard leaves (Sundberg & Royer, 1946). The amounts of sulfur from 2 vineyard samples (0.029 and 0.028 mg/cam 2) were not significantly different from the two laboratory samples (0.027 and 0.027 mg/cm2).…”
Section: Methodsmentioning
confidence: 99%
“…will suffice. Furnace capable of maintaining 900°C ., B. Auxiliary furnace which will accommodate the f 10/30 junctions of the combustion tube and the receiver and maintain 350°C ., C. Microcombustion tube, fused quartz, ACS specifications (3) but with a T 10/30 male joint formed on one end, D. Grote-tvpe borosilicate glass receiver (21) with f 10/30 standard joint, E, and spray trap, F.…”
Section: Many Methods and Variations Of Them Have Been Proposedmentioning
confidence: 99%
“…Some sulphur determinations were, therefore, done on the degradation products by the method of Sundberg and Royer (21). All analyses showed that sulphuric acid treated gluten contained about three times as much sulphur as the original gluten.…”
Section: Degradation Of Glzrtelz Szrlplzatementioning
confidence: 99%